The Transformation of Pancasila Admist Global Constitution Dynamics - Yunma Chusni Amalia (Indonesian Journal of Pancasila and Global Constitutionalism, 2025)
This study examines the transformation of Pancasila in facing the dynamics of global constitutionalism. Globalization has brought significant challenges to national ideologies, including Pancasila as the foundational philosophy of the Indonesian state. Through qualitative approach with literature study, this research analyzes the position of Pancasila within Indonesia's constitutional system and how its values transform in response to principles of global constitutional governance. The findings indicate that Pancasila undergoes reinterpretation and adaptation of its values without losing its ideological identity. This transformation manifests in human rights law reforms, adjustments to international treaties, and harmonization between Pancasila's collectivist values and global liberal individualism. This research recommends maintaining the flexibility of Pancasila's interpretation while preserving the essence of its noble values, and utilizing Pancasila as soft power in diplomacy and the formation of more just global governance.